2012
DOI: 10.3126/ajms.v2i3.5337
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Renal Function Using Cockcroft-Gault and Modification of Diet in Renal Disease Equations in Healthy South Indian Males – A pilot study

Abstract: Objective: To compare the estimated GFR (eGFR) calculated by CG and MDRD formulae and to study the correlation between body mass index (BMI) and eGFR in healthy South Indian men. Material & Methods:Healthy male volunteers were enrolled. eGFR was estimated by CG and MDRD equation and categorized as normal, mild, moderate, severe renal impairment and renal failure. Estimated clearance by these two methods was compared using paired student's t test. Correlations were performed with pearson's correlation test.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…There has been conflicting data in previous studies with respect to this association. A recent study done on 491 subjects from South India [12] had shown the same trend as that of us. It had also been described in other studies that higher BMI was consistently associated with lower MDRD [29] and CKD-EPI [30], while a few others had depicted a non-linear relationship between eGFR decline per year and BMI [31], [32].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…There has been conflicting data in previous studies with respect to this association. A recent study done on 491 subjects from South India [12] had shown the same trend as that of us. It had also been described in other studies that higher BMI was consistently associated with lower MDRD [29] and CKD-EPI [30], while a few others had depicted a non-linear relationship between eGFR decline per year and BMI [31], [32].…”
Section: Discussionsupporting
confidence: 83%
“…This can be due to different body physique of South Asian population. Similar findings of having an eGFR <90ml/min per 1.73 m 2 by CG and MDRD formula in more than 50% of the study subjects were found in two Indian studies [12], [19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These studies have variable outcomes 4,5 . However, not many studies have validated the use of these equations in the Indian population.…”
Section: Introductionmentioning
confidence: 99%